Mediatisation and datafication in the global COVID-19 pandemic: on the urgency of data literacy - Nguyen, Dennis (Media International Australia, 2021)
In the COVID-19 pandemic, societal discourses and social interaction are subject to rapid mediatisation and digitalisation, which accelerate datafication. This indicates urgency for increasing data literacy: individual abilities in understanding and critically assessing datafication and its social implications. Immediate challenges concern misconceptions about the crisis, data misuses, widening (social) divides and (new) data biases. Citizens need to be on guard in respect to the crisis’ impact on the next stages of the digital transformation.